The opposite of spoiled : raising kids who are grounded, generous, and smart about money - Lieber, Ron (Harper, an imprint of HarperCollinsPublishers, 2015)
"We may not realize it, but children are hyperaware of money. They have scores of questions about its nuances that parents often don't answer, or know how to answer well. But for Ron Lieber, a personal finance columnist and father, good parenting means talking about money with our kids much more often. When parents avoid these conversations, they lose a tremendous opportunity--not just to model important financial behaviors, but also to imprint lessons about what their family cares about most. Written in a warm, accessible voice, grounded in real-world stories from families with a range of incomes, The Opposite of Spoiled is a practical guidebook for parents that is rooted in timeless values. Lieber covers all the basics: the best ways to handle the tooth fairy, allowance, chores, charity, savings, birthdays, holidays, cell phones, splurging, clothing, cars, part-time jobs, and college tuition. But he also identifies a set of traits and virtues--like modesty, patience, generosity, and perspective--that parents hope their young adults will carry with them out into the world.In The Opposite of Spoiled, Ron Lieber delivers a taboo-shattering manifesto that will help every parent embrace the connection between money and values to help them raise young adults who are grounded, unmaterialistic, and financially wise beyond their years"--